Residential Mortgage Market in Economic and Social Development of Ukraine - Onysko Stefaniia M.; Sodoma Ruslana I. (Bìznes Inform, 2014)
The article studies tendencies of development of the residential mortgage market in Ukraine in the post-crisis period 2009 – 2012, identifies main tendencies of development of the Ukrainian mortgage market and conducts analysis of the level of mortgage interest rates. The article analyses the modern state of the mortgage market of Ukraine, dynamics of volumes of mortgage loans, their cost, structure of banks as mortgage creditors and cost of housing in Ukraine in the studied period. The article makes a number of offers on efficiency of mortgage, offers directions of financial support of rehabilitation of the market for solving housing problems of the population and identifies importance of state support of mortgage development.